Endothelial Microvesicles and Soluble Markers of Endothelial Injury in Critically Ill Newborns - Veronika Vítková; Martin Pánek; Petr Janec; Michaela Šibíková; Václav Vobruba; Martin Haluzík; Jan Živný; Jan Janota (Mediators of Inflammation)
Neonatal systemic inflammatory response and multiple organ dysfunction syndrome are the main postnatal insults influencing mortality and morbidity. Critically ill newborns with high predicted mortality are supported by extracorporeal membrane oxygenation (ECMO). Biomarkers of inflammatory response and endothelial injury can be used for early diagnosis and treatment of critical neonatal situations. The aim of our study was to explore plasma proteins and endothelial microvesicles as markers of inflammation and endothelial activation in newborns on ECMO and to compare them with healthy neonates. Thirteen newborns on ECMO and 13 healthy newborns were included in the study. Plasma soluble biomarkers were measured using multiplex immunoassay based on Luminex® xMAP multianalyte profiling platform. The total microvesicle count and plasma level of surface antigen-specific microvesicles were determined by flow cytometry. The plasma concentration of cell-derived microvesicles was measured using annexin-V labeling, and the endothelial origin of microvesicles was determined using lineage-specific antigen labeling of endothelial cell/microvesicle markers (endoglin/CD105, PECAM1/CD31, VEGFR2/CD309, and MadCAM1). Inflammatory markers (procalcitonin, IL-1β, IL-6, and IL-22) were increased in the ECMO group (P<0.01). The assessment of endothelial markers showed higher concentrations of endocan and angiopoietin-2 (P<0.01) in the ECMO group while VEGF in the ECMO group was significantly lower (P<0.01). In the ECMO group, the concentration of annexin-V-positive microvesicles (total microvesicles) and endothelial microvesicles expressing mucosal vascular addressin cell adhesion molecule 1 (MadCAM1) was increased (P=0.05). In summary, we found increased concentrations of soluble inflammatory and endothelial markers in the plasma of critically ill newborns with multiple organ dysfunction. Increased plasma concentrations of microvesicles may reflect the activation or damage of blood cells and vasculature including endothelial cells. The measurement of cell membrane-derived microvesicles may be added to the panel of established inflammatory markers in order to increase the sensitivity and specificity of the diagnostic process in critically ill newborns.